2013
DOI: 10.1038/labinvest.2013.97
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Wnt/β-catenin signaling in rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in children and accounts for about 5% of all malignant paediatric tumours. b-Catenin, a multifunctional nuclear transcription factor in the canonical Wnt signaling pathway, is active in myogenesis and embryonal somite patterning. Dysregulation of Wnt signaling facilitates tumour invasion and metastasis. This study characterizes Wnt/b-catenin signaling and functional activity in paediatric embryonal and alveolar RMS. Immunohistochemical assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 35 publications
3
31
2
Order By: Relevance
“…No consistent or robust differences in the number of differentiated (as assessed by ability to form myotubes and express the myogenic marker MF20) or senescent cells were observed in response to the stable expression of SFRP3 shRNAs in Rh28 cells (data not shown). Similarly, we saw no evidence of Wnt pathway activation (which is required for terminal myogenic differentiation) in aRMS cells stably expressing SFRP3 shRNAs, although in response to Wnt3a-conditioned media and LiCl (a GSK3β inhibitor) they retain the ability to activate β-catenin signaling, similarly to seen previously (15). However, in Rh28 cells both shRNAs caused a 16-22% increase in the percentage of cells accumulated in the G 1 phase of the cell cycle (Fig.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…No consistent or robust differences in the number of differentiated (as assessed by ability to form myotubes and express the myogenic marker MF20) or senescent cells were observed in response to the stable expression of SFRP3 shRNAs in Rh28 cells (data not shown). Similarly, we saw no evidence of Wnt pathway activation (which is required for terminal myogenic differentiation) in aRMS cells stably expressing SFRP3 shRNAs, although in response to Wnt3a-conditioned media and LiCl (a GSK3β inhibitor) they retain the ability to activate β-catenin signaling, similarly to seen previously (15). However, in Rh28 cells both shRNAs caused a 16-22% increase in the percentage of cells accumulated in the G 1 phase of the cell cycle (Fig.…”
Section: Resultssupporting
confidence: 82%
“…4K) were upregulated in response to both SFRP3 sh3 and sh5. Given the requirement for Wnt signaling during myogenic differentiation, we next examined the same tumors for evidence of Wnt pathway activation using nuclear β-catenin immunohistochemical staining and Axin2 expression (15, 33-35). While we could not detect an increase in nuclear β-catenin staining in those tumors bearing the SFRP3 shRNAs under conditions of dox treatment (data not shown), we did find Axin2 modestly upregulated (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is further supported by work in the mouse p53 −/− Fos −/− ERMS model, in which the canonical WNT/β-catenin pathway was actively suppressed by DKK1 and sFRP4 (30). Despite the active suppression of WNT/ β-catenin pathway in RMS, Annavarapu et al (31) recently showed that human ERMS and ARMS cell lines are responsive to exogenous WNT3A, inducing stabilization of β-catenin, altering proliferation, and enhancing differentiation in a subset of RMS cell lines. However, these studies failed to identify a role for the WNT/β-catenin pathway in modulating ERMS selfrenewal or in suppression of tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 63%